Desigualdad de los resultados educativos en el Perú. Un enfoque espacial - Sánchez Alcalde, Luis Amado (2025)
This paper examines inequality in educational outcomes in Peru through a spatial approach. Cluster analysis and spatial statistics were applied for the years 2007 and 2016. The results, based on the selected educational indicators, show that the country’s departments are grouped into at least four clusters, with little variation over time. In other words, departments with strong or weak performance in both the quality and quantity of education tend to remain largely unchanged from one year to the next. Although the data reflect realities prior to the pandemic, the findings provide a useful foundation for future research on progress in reducing educational inequality. In this context, sectoral policy should be implemented in ways that promote vertical equity and prioritize the regionalized and decentralized allocation of resources.